From strategic goals to business model innovation paths: an exploratory study - Marikka Heikkilä; Harry Bouwman; Jukka Heikkilä (Emerald, 2025)
Purpose
The purpose of this paper is to analyse how different strategic goals of (micro-, small- and medium-sized firms=SMEs) relate to the business model innovation (BMI) paths that SMEs take when improving their business.
Design/methodology/approach
The authors conducted 11 in-depth case studies involving SMEs innovating their business models (BMs).
Findings
The authors found evidence that strategic goals of SMEs (start new business, growth and profitability) lead them to alternative innovation path in terms of BM components affected. Growth seekers start from the right-hand side of a BM Canvas, while profitability seekers start from the back end, the left side of a Canvas; and new businesses adopt a cyclical approach considering BM components in turn, while at the same time redesigning and testing the BM. The findings of this study also indicate that all three paths gradually lead to improvement in several BM components.
Research limitations/implications
Findings indicate that a strategic management view in which strategic goals define BMI also applies to SMEs. The distinctive BMI paths that the authors identified provide evidence to suggest that, although the SMEs may not have an explicitly formulated strategy, their strategic goals determine the type of improvements they make to their BM. All three SME groups started their improvements from different BM components and changed several elements in their BMs in a specific order, forming distinctive BMI paths. Finally, to understand the BMI in SMEs better, more research is needed into BMI processes and into the way BMI is managed in SMEs.
Practical implications
The findings of this study help SMEs to anticipate the next steps in their path towards an improved BM. By mirroring their approach to the BMI paths, they can better manage their BM makeover process and focus on their innovation activities. For providers of BMI tools and methods, the study indicates which SME innovation tasks could be supported by tools and how the tools should be aligned with the BMI paths.
Originality/value
BMI is attracting growing attention in both research and practice. However, knowledge concerning BMI in SMEs is limited. The authors contributed to BMI research by focussing on the BMI paths of SMEs, i.e. the often sequential, non-linear and iterative steps taken to improve the business by making changes to specific BM components.